Outpatient Spine Clinic Utilization is Associated With Reduced Emergency Department Visits Following Spine Surgery. Issue 14 (15th July 2018) - Pak, Linda M.; Fogel, Harold A.; Chaudhary, Muhammad Ali; Kwon, Nicollette K.; Barton, Lauren B.; Koehlmoos, Tracey; Haider, Adil H.; Schoenfeld, Andrew J.
Abstract : Study Design: Review of TRICARE claims (2006–2014) data to assess Emergency Department (ED) utilization following spine surgery. Objective: The aim of this study was to determine utilization rates and predictors of ED utilization following spine surgical interventions. Summary of Background Data: Visits to the ED following surgical intervention represent an additional stress to the healthcare system. While factors associated with readmission following spine surgery have been studied, drivers of postsurgical ED visits, including appropriate and inappropriate use, remain underinvestigated. Methods: TRICARE claims were queried to identify patients who had undergone one of three common spine procedures (lumbar arthrodesis, discectomy, decompression). ED utilization at 30- and 90 days was assessed as the primary outcome. Outpatient spine surgical clinic utilization was considered the primary predictor variable. Multivariable logistic regression was used to adjust for confounders. Results: Between 2006 and 2014, 48, 868 patients met inclusion criteria. Fifteen percent (n = 7183) presented to the ED within 30 days postdischarge. By 90 days, 29% of patients (n = 14, 388) presented to an ED. The 30- and 90-day complication rates were 6% (n = 2802) and 8% (n = 4034), respectively, and readmission rates were 5% (n = 2344) and 8% (n = 3842), respectively. Use of outpatient spine clinic services significantly reduced the likelihood of ED utilization at 30 [odds ratio (OR) 0.48; 95% confidence interval (95% CI) 0.46–0.53] and 90 days (OR 0.55; 95% CI 0.52–0.57). Conclusion: Within 90 days following spine surgery, 29% of patients sought care in the ED. However, only one-third of these patients had a complication recorded, and even fewer were readmitted. This suggests a high rate of unnecessary ED utilization. Outpatient utilization of spine clinics was the only factor independently associated with a reduced likelihood of ED utilization. Level of Evidence: 3